Perjalanan Dan Perkembangan Videography Dari Ilmu Hingga Menjadi Sebuah Profesi - Nicholaus Wayong Kabelen (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2020)
Bob Kiger explained that videography is the activity of making video shows in pre-production, production and post-production the same as films. The location of the difference between film and videography technically lies in the tools used and the analysis bias of the media, the number of crew involved and the budget used during pre-production, production and post-production. Audio-visual media is one of the media that can be used in listening learning. This media can increase students' interest in learning because students can listen and see pictures. According to Sukiman (2012: 187-188), learning video media is a set of components or media that is able to display images at the same time. Print media at this time internet media is starting to dominate, easy access to data via mobile phones causes electrical media and print media to be new breakthroughs with media that previously could be enjoyed only by subscribing or watching television can now be opened on mobile phones or gadgets. Video makers also often create new types of videos according to creative thinking and experimentation with one type of video combined with other types of videos so that it becomes a new genre so that viewers are more interested and continue to watch the video shows that are presented. It is so easy to access that video makers are competing to create new things to be displayed in online media publications such as You Tube media. Video has the ability to provide information and describe an event quickly and directly and can also teach skills such as vlog videos that are popular today such as video-based social media You Tube, videos can also increase and develop time and can influence attitudes such as some viral videos, corruption documentary.